Legislative acts, presidential issuances, and judicial rulings pertaining to the University of the Philippines an annotated compilation - Ferrer, Resurreccion N., 1937-
A historico-chronological approach sets the pace and tempo of this study, from the passage of the University Charter up to 1978. In the process were examined closely pertinent legislative enactments such as Acts (so-called Public Laws), Commonwealth Acts, Republic Acts, and Presidential Decrees. Other issuances from the Chief Executive were also looked into, like Executive Orders, Administrative Orders, Proclamations, and Letters of Instructions.
All these materials which were mostly xeroxed in toto and annotated for greater convenience comprise this brief survey. They show how the University began as a compact institution run by the American colonizers, and how it was later transformed by Filipino legislators, executives, and policy-makers into a University of the People through legislative enactments, presidential issuances, and pertinent judicial rulings.
Early legislative enactments concern the government and administration of the University, the opening and encouragement of scholarships in various fields with emphasis on veterinary and biological sciences. Institution of necessary courses were likewise tackled by the various legislative Acts. The budget of the University was similarly touched upon by the legislature.
Interspersed within the condensation are the judicial rulings that somehow set precedents for future policy actions for the University's administrators.
Judicial Decisions were also examined as well as the relevant Opinions of the Secretary of Justice.
Many of the legislative enactments are either new laws or amendments to the University's Charter (Act No. 1870).
Personnel matters, tenure, and contracts are the topics delved upon in the judicial rulings. These have served useful and invaluable precedents for the University.
Subsequent chapters after the compact "legal history' of the University examine in greater detail the different legislative enactments, presidential issuances, and pertinent judicial rulings.
The first part of the study is a condensation of the University's history, enumerating in greater detail the law that established the University of the Phlippines (Act No. 1870) as well as the laws that molded it, chartered its course, and shaped its destiny.
The growth and gradual expansion of the University was initiated by the policy-makers as a necessary response to the needs of the Filipino people.
The history of the University of the Philippines, from the legal viewpoint, properly begins in 1908 when its Charter (Act No. 1870) was passed.
The last portion contains miscellaneous items that are supplementary to the body of the study. These include the relevant Opinions of the Secretary of Justice and a table of the yearly budgetary appropriations for the University.
The Opinions of the Secretary of Justice on many inquiries sent by the University Presidents likewise provide precedent-setting pronouncements that live to this day.
The Presidential Decrees concern the opening of new and additional Units to the University.
Thus, from its founding, the legislative enactments that were to affect the University considerably were called Acts (Public Laws), later Commonwealth Acts, the republic Acts, and Presidential Decrees. The others consisted of Presidential issuance such as Executive Orders, Administrative Orders, Proclamations and Letters of instructions.
Thesis (M.L.S)--University of the Philippines, Diliman
Typescript.
Keywords: University of the Philippines--Legislation.